A comparison of statistical and decision-making techniques in marketing mix evaluation. Issue 10 (11th November 2019) - Shokrani, Mahsa; Haghighi, Mohammad; Paricheh, Morteza; Shokrani, Mina
Abstract : Purpose: Although customer satisfaction (CS) has been evaluated through using statistical and decision-making techniques so far, no research, to the best of the authors' knowledge, has been conducted for implementing both groups simultaneously and clarifying the different or similar aspects of the results given by these techniques. The purpose of this paper is to compare the techniques and clarify these unknown aspects. Design/methodology/approach: First, the effect of the elements related to service marketing mix on CS was examined by using structural equation model (SEM). Then, the statistical methods such as Friedman test (FT) and SEM, and decision-making technique such as Analytical Hierarchy Process (AHP) were systematically compared for prioritizing the elements of service marketing mix. The sample included 159 special customers of an anonymous bank in Bojnurd, Iran. The reliability of the questionnaire was confirmed by using Cronbach's α ( r =0.934). In addition, SPSS, Expert Choice and Smart PLS software were used. Findings: Based on the results, FT and AHP method had exactly the same ranking for the elements of the marketing mix, as well as almost identical relative weights. The ranking included people, process, product, physical evidence, place, price and promotion, respectively, while the SEM technique had very different outcomes. Finally, none of the methods could assure the marketer to come to a reliable decision separately. Originality/value: In this study, the authors' contribution is the understanding of the role of an effective marketing mix evaluation technique selection on marketing strategy. Different techniques had different and in some cases even contradicting outcomes.